MODERN METHODS FOR THE INVESTIGATION OF THYROID DISEASES - K. Baizhanova; D. Karim; B. Akzhol; O. Tashniyazov; Z. Djumataeva (Yassawi Journal of Health Sciences, 2026)
Objective: To review the main methodologies, datasets, and performance indicators of modern research approaches used in the diagnosis of thyroid diseases. Materials and Methods: A review of the literature published between 2021 and 2026 was conducted to assess the capabilities of contemporary diagnostic methods for thyroid diseases. In all thyroid disorders, a hormonal panel is performed to determine serum levels of thyroid hormones and thyroid-stimulating hormone (TSH). In thyroiditis, autoimmune markers, including antibodies against thyroid peroxidase (TPO), thyroglobulin (Tg), and TSH receptors (TRAb), are measured. Carcinoembryonic antigen (CEA) serves as a biomarker for medullary thyroid carcinoma and carcinoid tumors. Elevated calcitonin levels are characteristic of medullary thyroid carcinoma. Increased thyroglobulin concentrations are observed in destructive thyroid processes and metastatic disease. Fine-needle aspiration biopsy (FNAB) is performed to obtain histological samples from thyroid nodules. When cytological findings are inconclusive, molecular genetic testing is carried out to identify mutations in genes such as BRAF, RAS, and RET/PTC. In addition, in silico approaches are used to identify target genes comprising 19 microRNAs whose expression profiles vary depending on the type of thyroid tumor. Ultrasonography (US), a non-invasive, relatively inexpensive, and real-time imaging technique, is widely used for the early detection and differential diagnosis of thyroid diseases. Ultrasound-guided fine-needle aspiration biopsy is recommended for deeply located thyroid nodules. Since malignant lesions are generally denser and stiffer than benign ones, ultrasound elastography (elastometry) can determine the nature of thyroid nodules with an accuracy of approximately 95–96%, often reducing the need for biopsy. Doppler ultrasonography is used to evaluate the vascularization of the thyroid gland and its nodules. Thyroid scintigraphy employs radioisotope scanning to assess the functional activity of nodular lesions. In recent years, computer-aided diagnostic systems and high-accuracy neural networks based on ultrasound images have been increasingly applied to improve diagnostic accuracy and significantly reduce the time required for clinical decision-making. Conclusion: Compared with conventional diagnostic approaches, molecular genetic testing, advanced ultrasonographic techniques, computer-aided diagnostic systems, and high-accuracy neural networks provide superior diagnostic accuracy, sensitivity, and specificity in the investigation of thyroid diseases.